Meta-analysis of the effect of glycerin inclusion in dairy cattle diet on milk fatty acid profile - Torres, Rodrigo N. S. [UNESP]; Bertoco, João P. A. [UNESP]; De Arruda, Maria C. G. [UNESP]; Rodrigues, Julia L. [UNESP]; Coelho, Larissa M. [UNESP]; Paschoaloto, Josimari R. [UNESP]; De Almeida Júnior, Gercílio A.; Ezequiel, Jane M. B. [UNESP]; Almeida, Marco T. C. (Oxford University Press (OUP), 2021)
The use of glycerin in diets for dairy cows initially emerged as an alternative for the prevention and control of ketosis. However, despite some controversy, there are still several studies associating glycerin with increases in daily milk yield, with possible changes in its constituents. Therefore, the objective of this study was to evaluate, using a meta-analysis approach, the effect of glycerin inclusion in dairy cow diets on milk fatty acid. Twenty-two peer-reviewed publications with 66 treatment means were included in data set. The effect of glycerin inclusion in diet (treatment) were evaluated using random-effect models to examine the weighted mean differences (WMD) between a control diet (without glycerin in the diet) and the treatment diet. Heterogeneity was explored by meta-regression and subgroup analysis performed for: genetic type; days in milk; experimental period; glycerin in diet; glycerin type and concentrate in diet. Inclusion of glycerin in the diet increased the digestibility of dry matter and protein, as well as ruminal propionate. It did not affect dry matter intake (P = 0.351) and milk yield (P = 0.730). The effect of glycerin inclusion on the milk fat yield is dependent on the genetic group, in which Holstein (WMD = -0.04 kg/d; P = 0.010) and Holstein-crossbreed (WMD = -0.10 kg/d; P < 0.0001) cows produced less fat in milk compared to Jersey cows, when glycerin was included in the diets. Glycine inclusions of up to 100 g/kg in the diet of dairy cows did not negatively affect milk production and composition. However, inclusions above 150 g/kg of glycerin in the diet reduced the concentration of fat, and of unsaturated, monounsaturated, polyunsaturated fatty acids and conjugated linoleic acid (CLA C18: 2 cis-9 and trans-11) in milk. The results reported in our meta-analysis does not demonstrate the effectiveness of glycerin in improving the composition of milk and a group of fatty acids of importance for human health such as C18: 2 cis-9, trans-11 CLA.
Keywords: biodiesel; fat milk; fatty acid; glycerol